Week 4 response predicts sustained virological response to all-oral direct-acting antiviral-based therapy in cirrhotic patients with hepatitis C virus genotype 3 infection. (June 2017) - Pineda, J.A.; Morano-Amado, L.E.; Granados, R.; Macías, J.; Téllez, F.; García-Deltoro, M.; Ríos, M.J.; Collado, A.; Delgado-Fernández, M.; Suárez-Santamaría, M.; Serrano, M.; Miralles-Álvarez, C.; et al.
Abstract: Objective: The aim of this study was to determine the predictive capacity of response at treatment week (TW) 4 for the achievement of sustained virological response 12 weeks after the scheduled end of therapy date (SVR12 ) to treatment against hepatitis C virus (HCV) genotype 3 (GT3) infection with all-oral direct-acting antiviral (DAA) -based regimens. Patients and methods: From a prospective multicohort study, HCV GT3-infected patients who completed a course of currently recommended DAA-based therapy at 33 Spanish hospitals and who had reached the SVR12 evaluation time-point were selected. TW4 HCV-RNA levels were categorized as target-not-detected (TND), below the lower limit of quantification (LLOQTD ) and ≥LLOQ. Results: A total of 123 patients were included, 86 (70%) received sofosbuvir/ daclatasvir ± ribavirin, 27 (22%) received sofosbuvir/ ledipasvir/ ribavirin and 10 (8.1%) received sofosbuvir/ ribavirin, respectively. In all, 114 (92.7%) of the 123 patients presented SVR12 in an on-treatment approach, but nine (7.3%) patients relapsed, all of them had presented cirrhosis at baseline. In those who achieved TND, LLOQTD and ≥LLOQ, SVR12 was observed in 81/83 (98%; 95% CI 91.5%–99.7%), 24/28 (85.7%; 95% CI 67.3%–96%) and 9/12 (75%; 95% CI 42.8%–94.5%), respectively; p(linear association) 0.001. Corresponding numbers for subjects with cirrhosis were: 52/54 (96.3%; 95% CI 87.3%–95.5%), 14/18 (77.8%; 95% CI 52.4%–93.6%) and 7/10 (70%; 95% CI 34.8%–93.3%); p 0.004. Conclusions: TW4-response indicates the probability of achieving SVR12 to currently used DAA-based therapy in HCV genotype 3-infected individuals with cirrhosis. This finding may be useful to tailor treatment strategy in this setting.